Dietary grape seed proanthocyanidins improved growth, immunity, antioxidant, digestive enzymes activities, and intestinal microbiota of juvenile hybrid sturgeon (Acipenser baeri Brandt ♀ × A. schrenckii Brandt ♂). (12th September 2021) - Xu, Guanling; Xing, Wei; Li, Tieliang; Yu, Huanhuan; Wei, Shibo; Jiang, Na; Ma, Zhihong; Luo, Lin
Abstract: An 8‐week growth trial was performed to evaluate the effects of grape seed proanthocyanidins (GSPs) on growth, digestive enzymes, body composition, intestinal microbiota, serum immunological, anti‐oxidative and biochemical parameters of juvenile hybrid sturgeon ( Acipenser baeri Brandt ♀ ×  A. schrenckii Brandt ♂). Fish were randomly divided to control, GSPs‐50 and GSPs‐100 groups, which were fed with a basal diet and basal diet supplemented with 50 and 100 mg/kg GSPs, respectively. Growth performance and digestive enzymes were improved by GSPs in sturgeon ( p  < .05). Lysozyme was clearly increased in serum when sturgeon fed with GSPs diets, while the thiobarbituric acid reactive substances (TBARS) displayed opposite trend ( p  < .05). Myeloperoxidase and glutathione peroxidase in serum of GSPs‐50 were higher than control and GSPs‐100 ( p  < .05). Serum parameters showed alanine aminotransferase, alkaline phosphatase and γ‐glutamyl transpeptidase of GSPs‐50 were lower than control ( p  < .05). Compared with the control treatment, GSPs‐100 reduced alanine aminotransferase and γ‐glutamyl transpeptidase and increased aspartate aminotransferase and lactate dehydrogenase ( p  < .05). High‐throughput sequencing revealed that adding 50 mg/kg GSPs not only modified the microbiota diversity, but also reduced the relative abundance of Aeromonas in sturgeon intestine. In conclusion, GSPs are a promising feed additive to promote growth, immunity, antioxidant and digestive enzyme activities and improve serum biochemical parameters and intestinal microbiota of hybrid sturgeon.